Role-Playing Method to Enhance Children's Communication Skills and Cognitive Development - Y. Yuliatin; I. Ismail (Golden Ratio of Data in Summary, 2026)
This study aims to analyze the implementation of the role-playing method in improving children's communication skills and cognitive development in a kindergarten in Tahunan Village. The background of this research is the importance of contextual and active learning for early childhood, where role-playing can serve as a meaningful learning medium. This study employs a qualitative approach with a case study design. Data were collected through in-depth interviews with teachers, the school principal, and students’ parents, participatory observation, and documentation of activities. The results indicate that the role-playing method encourages children to interact actively, improves their communication abilities, symbolic thinking, and simple problem-solving skills. This activity aligns with the concept of the Zone of Proximal Development proposed by Lev Vygotsky, where children are able to reach their cognitive potential through teacher guidance and social interaction. In conclusion, the role-playing method is effective as an enjoyable learning strategy that supports the social and cognitive development of early childhood learners.